2020
DOI: 10.1080/13657305.2020.1857469
|View full text |Cite
|
Sign up to set email alerts
|

Salmon trout, the forgotten cousin?

Abstract: This file was downloaded from BI Open, the institutional repository (open access) at BI Norwegian Business School https://biopen.bi.no.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 69 publications
0
6
0
1
Order By: Relevance
“…Their results strengthen the relevance of the futures market for hedging salmon transactions. It is further helpful in our context that recent results by Landazuri-Tveteraas et al (2021) and Salazar and Dresdner (2021) present strong evidence for market integration in the salmon market and the hypothesis that there is in fact a global market for salmon.…”
Section: Introductionmentioning
confidence: 73%
“…Their results strengthen the relevance of the futures market for hedging salmon transactions. It is further helpful in our context that recent results by Landazuri-Tveteraas et al (2021) and Salazar and Dresdner (2021) present strong evidence for market integration in the salmon market and the hypothesis that there is in fact a global market for salmon.…”
Section: Introductionmentioning
confidence: 73%
“…This is particularly important for salmon since there is a number of issues with respect to its environmental sustainability that can at least partly be addressed by certification. 94 e Asche and Bjørndal 17 provide more detail about the growth of the industry, while Landazuri-Tveteraas 98 provide more information about the trout. The regulatory system for the two species is identical, and it is the same licence required to farm salmon or trout.…”
Section: Discussionmentioning
confidence: 99%
“…Better access to microdata has made it possible for researchers to suggest different approaches as to how total sales at the firm level can be attributed to different margins of trade. Some relevant examples for trade in general are Bernard et al (2007) , Lawless (2010) , Hornok and Koren (2015) , Asche et al (2021b) , and Landazuri-Tveteraas et al, 2021a , Landazuri-Tveteraas et al, 2021b . Specific to seafood, Straume et al (2020b) investigates if trade margins for aquaculture products differ from trade margins in wild seafood products beyond just total export value.…”
Section: Margins Of Tradementioning
confidence: 99%
“…The fact that the price effects have different signs is notable, as a number of studies have reported that the salmon market is highly integrated ( Landazuri-Tveteraas et al, 2021a , Landazuri-Tveteraas et al, 2021b ; Salazar and Dresdner, 2021 ). However, Landazuri-Tveteras et al, (2018) show that the degree of price transmission varies significantly between product forms, and, as such, this result highlights the fact that the short-run dynamics vary by product form.…”
Section: Trade Margins and Lockdown Stringencymentioning
confidence: 99%
See 1 more Smart Citation